2022
DOI: 10.1002/mp.15644
|View full text |Cite
|
Sign up to set email alerts
|

Range uncertainty reductions in proton therapy may lead to the feasibility of novel beam arrangements which improve organ‐at‐risk sparing

Abstract: In proton therapy, dose distributions are currently often conformed to organs at risk (OARs) using the less sharp dose fall-off at the lateral beam edge to reduce the effects of uncertainties in the in vivo proton range. However, range uncertainty reductions may make greater use of the sharper dose fall-off at the distal beam edge feasible, potentially improving OAR sparing. We quantified the benefits of such novel beam arrangements. Methods: For each of 10 brain or skull base cases, five treatment plans robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This ensures that the prescribed dose is delivered to the tumour, but at the expense of an extra dose to the surrounding healthy tissue. In addition, selection of beam angles is limited to avoid the risk of overshoots to high-risk organs 4 , 5 . Thus, it is highly desirable to increase the accuracy and adaptation potential of PT, especially for moving tumors and patients with implants or target regions affected by anatomical changes.…”
Section: Introductionmentioning
confidence: 99%
“…This ensures that the prescribed dose is delivered to the tumour, but at the expense of an extra dose to the surrounding healthy tissue. In addition, selection of beam angles is limited to avoid the risk of overshoots to high-risk organs 4 , 5 . Thus, it is highly desirable to increase the accuracy and adaptation potential of PT, especially for moving tumors and patients with implants or target regions affected by anatomical changes.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of target margins that are associated with range uncertainties, enabled by the use of 11 C beams, apart from reducing the doses to the adjacent structures by default, might further improve the flexibility and quality of treatment by enabling irradiation from different angles. A recent study 22 has shown further brainstem NTCP decrease from using novel proton beam arrangements, enabled by the reduced range margins. As the authors have shown, new beam arrangements might also enable the possibility of redistributing the LET distributions in the target and increasing its mean value.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced range uncertainties guaranteed with 11 C beams, apart from reducing the doses to the adjacent structures by default, might further improve the exibility and quality of treatment by enabling irradiation from different angles. A recent study 22 has shown further brainstem NTCP decrease from using novel proton beam arrangements, enabled by the reduced range margins. As the authors have shown, new beam arrangements might also enable the possibility of redistributing the LET distributions in the target and increasing its mean value.…”
Section: Discussionmentioning
confidence: 99%